2016
DOI: 10.2147/ott.s110595
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer patients may have an increased risk of coexisting advanced colorectal neoplasms

Abstract: Background/aimsPatients being treated for prostate cancer (PCa) have an increased risk of developing colorectal cancer. However, whether PCa patients are inherently at a higher risk of colorectal neoplasms (CRNs) is unknown. We aimed to investigate the risk of CRNs in PCa patients.Materials and methodsPatients who had been diagnosed with PCa at a tertiary medical center and had colonoscopy within 1 year of the PCa diagnosis were investigated. Patients were propensity-matched 1:2 by age and body mass index to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, it is conceivable that men with prostate cancer may be more susceptible to the development of CRC. A lower risk of CRC after prostate cancer was reported in one study [ 42 ] whereas others reported an increased risk of CRC after a diagnosis of prostate cancer [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is conceivable that men with prostate cancer may be more susceptible to the development of CRC. A lower risk of CRC after prostate cancer was reported in one study [ 42 ] whereas others reported an increased risk of CRC after a diagnosis of prostate cancer [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,34 According to Kim et al, males diagnosed with colorectal cancer have a higher risk for prostate cancer 34 while people with prostate cancer had a higher risk of having advanced abnormal growths in the colon. 33…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that colon and prostate cancer are connected and patients who have had prostate cancer in the past may be more likely to have colorectal cancer. 33,34 According to Kim et al, males diagnosed with colorectal cancer have a higher risk for prostate cancer 34 while people with prostate cancer had a higher risk of having advanced abnormal growths in the colon. 33…”
Section: Skills Acquisition and Specializationmentioning
confidence: 99%